Green Visions, Symbolic Missions? Analyzing the Gap in SDG 13 Implementation in Indonesian Schools - Hammam; Manar Abdurra'uf Fatin (ISEJ : Indonesian Science Education Journal, 2025)
This study examines how vision and mission statements of state junior high schools in Salatiga, Indonesia, reflect climate change awareness and support Sustainable Development Goal (SDG) 13: Climate Action. Using qualitative content analysis of official school documents, it evaluates the presence of environmental themes and how these are translated from vision into mission. The findings show that all schools incorporate environmental themes, indicating strong awareness. However, only 20% demonstrate high alignment through structured and measurable programs, while 40% show partial implementation and the remaining 40% remain largely symbolic. These results suggest that SDG 13 is predominantly interpreted at the level of awareness, with limited integration of mitigation and adaptation strategies. A clear gap exists between institutional intention and operational practice. This study highlights vision–mission alignment as an indicator of school readiness and underscores its implications for strengthening environmental and science education in schools.